(untitled) (Research, Society and Development, 2020)
The study aims to define the criminal and socioeconomic profile of the incarcerated women on the Maternal and Children Unit of Ananindeua-PA, in order to understand the purpose of involvement of these women in crime. Thereupon, a quantitative research was put in practice, in addition to a descriptive analysis technique. The data on the criminal and socioeconomic profile of the detainees was obtained through a semi-structured interview with the pregnant and postpartum women of the Maternal and Child Unit (MCU) of the Ananindeua-PA Women’s Recovery Center, in the period of 03/24/2017 to 03/27/2017. The results presented that the majority of women incarcerated in the MCU are poor, of black race / color, with low income, have committed the crime of trafficking, and lived in conditions of socioeconomic vulnerability.